2019
DOI: 10.1107/s2053229619002961
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of noncovalent interactions in antiseptic quaternary ammonium surfactant Miramistin

Abstract: The molecular and crystal structure of the widely used antiseptic benzyldimethyl-{3-[(1-oxotetradecyl)amino]propyl}ammonium chloride monohydrate (Miramistin, MR), C 26 H 47 N 2 O + ÁCl À ÁH 2 O, was determined by a single-crystal X-ray diffraction study and analyzed in the framework of the QTAIM (quantum theory of atoms in molecules) approach using both periodic and molecular DFT (density functional theory) calculations. The various noncovalent intermolecular interactions of different strengths were found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Also, its terminal aliphatic groups penetrated deeper into the hydrophobic core of the bilayer (Figure D). In contrast to other CA species, miramistin (MIR) exhibits a “hook”-shaped conformation anchored by a single long hydrophobic tail inside the membrane with its charged moiety located near the head groups of lipids (Figure C), as proposed earlier …”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Also, its terminal aliphatic groups penetrated deeper into the hydrophobic core of the bilayer (Figure D). In contrast to other CA species, miramistin (MIR) exhibits a “hook”-shaped conformation anchored by a single long hydrophobic tail inside the membrane with its charged moiety located near the head groups of lipids (Figure C), as proposed earlier …”
Section: Resultsmentioning
confidence: 69%
“…In contrast to other CA species, miramistin (MIR) exhibits a "hook"-shaped conformation anchored by a single long hydrophobic tail inside the membrane with its charged moiety located near the head groups of lipids (Figure 1C), as proposed earlier. 25 Remarkably, all of the studied antiseptics neither disintegrated the membrane nor solubilized individual lipids or pulled them from the bilayer plane even in the simulations with the highest concentration of CA (1:4 antiseptic/lipid ratio). We neither observed the formation of transient transmembrane pores nor membrane protrusions at the investigated timescale up to 30 μs.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…The second approach, the most consistent, typically includes “true” periodic calculations taking into account the crystalline structure of studied systems. It is perfectly correct for highly symmetrical crystals (see reviews and recent works ) but has certain limitations for less symmetric, disordered molecular crystals, and crystallosolvates. Notably, this approach is time-consuming, and this is a certain limitation especially for the crystals with low point symmetry …”
Section: Resultsmentioning
confidence: 99%
“…For modeling the organic layers, their thicknesses were set equal to those determined from the PXRD data for each compound. The initial conformation of MR molecules within these layers was taken as identical to the bent conformation, with the head group inclined to the long-chain alkyl tail, revealed previously by single-crystal XRD study [ 27 ] ( Figure S2 ). Importantly, the DFT calculations have showed that this conformation of the MR cation, stabilized by intramolecular interactions, is a preferable one also in the water surrounding [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The distinctive feature of MR molecular skeleton is the presence of amidopropyl linker, which is capable of playing the role of a hinge between the ammonium head and aliphatic tail ( Figure 1 ). The conformation preference of this molecule and peculiarities of the packing geometry of its hydrophilic and hydrophobic parts have recently been determined by single-crystal X-ray diffraction [ 27 ]. Considering the potential usage of MR–MoS 2 hybrid composites as combined photothermal and antiseptic materials, it was of utmost interest to study the mutual affinity of the components, in particular, to reveal the conditions for filling the MoS 2 interlayer gaps with MR molecules, which have never been reported before.…”
Section: Introductionmentioning
confidence: 99%